Uso pedagógico de las tecnologías de la información y la comunicación (TIC’s) por parte de los docentes para desarrollar aprendizajes significativos en los estudiantes de educación general básica de la escuela Zoila Ugarte de Landívar del cantón El Guabo, provincia de El Oro, periodo lectivo 2013 – 2014. - La Rosa Reyes, Olga Betzabeth (2015)
School Zoila Ugarte Landívar is an institution to provide excellent education to students using new technologies and teaching methodologies that have facilitated the development of some commonly performed tasks that teachers, students and administrators but because they also open opportunities to affect the learning environments which are held educational processes and methods used for teaching and learning and even change the roles previously played each of the actors involved in the educational process. Through the work of titling the "pedagogical use of information technology and communication (ICT's) was proposed by teachers to develop meaningful learning in students of basic education school Zoila Ugarte Landívar Canton El Guabo province of gold, academic year 2013 - 2014 "as in education, computer literacy in the evolution of science and technology should include aspects such as its use as a means of expression beyond the limits of the classroom and to develop proposals in other disciplines activities and appropriation of concepts and characteristics of the computing discipline methodologies, technologies of information and communication technologies (ICT) can contribute to universal access to education, equality in education, the exercise of teaching and learning quality and professional development of teachers as well as more efficient management and administration of the education system management. Therefore the pedagogical use of information technologies and communication by teachers allowed to develop meaningful learning in students of basic general education Zoila Ugarte Landívar School Canton El Guabo.